2021
DOI: 10.3390/biom11111561
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Disulfiram for Targeting of Glioblastoma Stem Cells: An In Vitro Study

Abstract: Mesenchymal glioblastoma stem cells (GSCs), a subpopulation in glioblastoma that are responsible for therapy resistance and tumor spreading in the brain, reportedly upregulate aldehyde dehydrogenase isoform-1A3 (ALDH1A3) which can be inhibited by disulfiram (DSF), an FDA-approved drug formerly prescribed in alcohol use disorder. Reportedly, DSF in combination with Cu2+ ions exerts multiple tumoricidal, chemo- and radio-therapy-sensitizing effects in several tumor entities. The present study aimed to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Further, we analyzed the differentially upregulated or downregulated genes of the above two kinds of cells, and the results showed that 201 genes were downregulated and 78 genes were upregulated (including ALDH1A3 ) ( Figure 4 B). Studies have shown that ALDH1A3 plays an important role in the mesenchymal differentiation and malignant progression of GBM cells [ 43 , 44 , 45 , 46 ]. Our previous studies showed that ALDH1A3 is one of the key metabolic enzymes involved in the occurrence and development of GBM [ 25 , 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, we analyzed the differentially upregulated or downregulated genes of the above two kinds of cells, and the results showed that 201 genes were downregulated and 78 genes were upregulated (including ALDH1A3 ) ( Figure 4 B). Studies have shown that ALDH1A3 plays an important role in the mesenchymal differentiation and malignant progression of GBM cells [ 43 , 44 , 45 , 46 ]. Our previous studies showed that ALDH1A3 is one of the key metabolic enzymes involved in the occurrence and development of GBM [ 25 , 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We were not able to translate the numerous encouraging preclinical results to the clinical setting . Several studies have indicated a synergistic effect between temozolomide (or other alkylating agents) and disulfiram, although 1 study found that temozolomide somehow antagonized the effects of disulfiram . It has been suggested that disulfiram-copper induce MGMT inhibition, but also increased replication stress and DNA damage, hence there are arguments that SOC plus disulfiram and copper could potentiate treatment effects, both for patients with unmethylated and with hypermethylated MGMT promoter .…”
Section: Discussionmentioning
confidence: 96%
“… 4 , 8 , 13 , 14 , 15 , 16 Several studies have indicated a synergistic effect between temozolomide (or other alkylating agents) and disulfiram, 8 , 16 , 33 although 1 study found that temozolomide somehow antagonized the effects of disulfiram. 34 It has been suggested that disulfiram-copper induce MGMT inhibition, but also increased replication stress and DNA damage, hence there are arguments that SOC plus disulfiram and copper could potentiate treatment effects, both for patients with unmethylated and with hypermethylated MGMT promoter. 8 , 16 , 19 , 35 The complete lack of positive signal in our trial indicate that this has no clinical relevance in patients with recurrent GB.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, drugs related to cuproptosis can also be used to the treatment of tumors. Disulfiram, a copper ionophore, targeted glioblastoma stem cells ( 87 ). Elesclomol can targeted treatment of melanoma ( 88 ).…”
Section: Discussionmentioning
confidence: 99%